Measuring power - Frankenberg, Elizabeth; Thomas, Duncan (International Food Policy Research Institute, 2001)
This paper focuses on dynamics within couples, although the authors recognize that dynamics among extended family members and across generations are of substantial interest. Decisions about resource allocations, control over economic resources, whether and how much one works, are all examined.